2018
DOI: 10.1128/aem.02084-17
|View full text |Cite
|
Sign up to set email alerts
|

A Canonical Biotin Synthesis Enzyme, 8-Amino-7-Oxononanoate Synthase (BioF), Utilizes Different Acyl Chain Donors in Bacillus subtilis and Escherichia coli

Abstract: BioF (8-amino-7-oxononanoate synthase) is a strictly conserved enzyme that catalyzes the first step in assembly of the fused heterocyclic rings of biotin. The BioF acyl chain donor has long been thought to be pimeloyl-CoA. Indeed, the and enzymes have been shown to condense pimeloyl-CoA with l-alanine in a pyridoxal 5'-phosphate-dependent reaction with concomitant CoA release and decarboxylation of l-alanine. However, recent studies of and suggested that the BioF proteins of the two bacteria could have differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Previous studies have shown that B. subtilis BioF specifically accepts only pimeloyl-CoA as acyl donor, whereas pimeloyl-ACP is inactive both in vivo and in vitro 12 . In contrast, E. coli BioF accepts either of the pimeloyl-thioesters, although pimeloyl-ACP is strongly favored.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies have shown that B. subtilis BioF specifically accepts only pimeloyl-CoA as acyl donor, whereas pimeloyl-ACP is inactive both in vivo and in vitro 12 . In contrast, E. coli BioF accepts either of the pimeloyl-thioesters, although pimeloyl-ACP is strongly favored.…”
Section: Resultsmentioning
confidence: 97%
“…After preparation of the resting cell suspensions in minimal medium lacking a carbon source, various dicarboxylic acids were added followed by incubation for 12-16 h. The culture media were concentrated tenfold and spotted on plates containing strain E. coli ER90 to assay for biotin/DTB production. Unlike B. subtilis which directly incorporates exogenous pimelate into biotin 6,12 , A. tumefaciens failed to incorporate pimelate into biotin/DTB but rather used glutarate or compounds readily converted to glutarate to synthesize the pimelate precursor (Fig. 8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BioW was reported essential in B. subtilis and converts pimelate to pimeloyl-CoA (Manandhar and Cronan 2017). Furthermore, it was found that BioF of B. subtilis specifically used pimeloyl-CoA, whereas E. coli BioF also used pimeloyl-[acp] (Manandhar and Cronan 2018). Recently, it was reported that C. acetobutylicum was able to grow in defined medium without biotin (Li et al 2013; Yang et al 2016), although carry-over of biotin in the method used cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%